2018
DOI: 10.12669/pjms.346.15349
|View full text |Cite
|
Sign up to set email alerts
|

Meconium stained liquor and its neonatal outcome

Abstract: Objective:To determine the maternal factors and neonatal outcome of pregnancy complicated by meconium stained amniotic fluid.Methods:This one year retrospective study was conducted at the Agha Khan Hospital for Women-Garden Campus, it is a secondary care private teaching hospital. Demographics information included gestational age, gender and birth weight of baby, medical and obstetric complications during pregnancy, mode of delivery, neonatal outcome (Meconium Aspiration Syndrome (MAS) and need for admission i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
28
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 9 publications
7
28
5
Order By: Relevance
“…Important data from our study showed that there are significant concerning the number of pregnancies (P-value = 0.004) and a number of times (P-value = 0.001). In comparison to other studies which showed no significant association was found with parity such as a retrospective study was conducted at the Agha Khan Hospital showed a P-value = 0.36 [11] and a Cross-sectional study carried in-hospital birth centre in the city of São Paulo, South-eastern Brazil showed P-value = 0.6800 [12]. Normal delivery was two times the caesarean section in a patient with MSAF, As to a study done by, Gupta SN et al reported that 22% of MSAF group had normal vaginal delivery while, caesarean section delivery was 66% among MSAF group Caesarean section was seen more in MSAF group; also Rajlaxmi Mundhra and Manika Agarwal found Caesarean section rates were nearly double in cases (49.09%) of MSAF Moreover in a study done by J Pak Med Assoc showed that Among 250 women with MSAF 205 women delivered by caesarean section and 35 women had vaginal deliveries, in comparison.…”
Section: Discussioncontrasting
confidence: 82%
“…Important data from our study showed that there are significant concerning the number of pregnancies (P-value = 0.004) and a number of times (P-value = 0.001). In comparison to other studies which showed no significant association was found with parity such as a retrospective study was conducted at the Agha Khan Hospital showed a P-value = 0.36 [11] and a Cross-sectional study carried in-hospital birth centre in the city of São Paulo, South-eastern Brazil showed P-value = 0.6800 [12]. Normal delivery was two times the caesarean section in a patient with MSAF, As to a study done by, Gupta SN et al reported that 22% of MSAF group had normal vaginal delivery while, caesarean section delivery was 66% among MSAF group Caesarean section was seen more in MSAF group; also Rajlaxmi Mundhra and Manika Agarwal found Caesarean section rates were nearly double in cases (49.09%) of MSAF Moreover in a study done by J Pak Med Assoc showed that Among 250 women with MSAF 205 women delivered by caesarean section and 35 women had vaginal deliveries, in comparison.…”
Section: Discussioncontrasting
confidence: 82%
“…MSAF was associated with poor perinatal outcomes such as meconium aspiration syndrome. A previous study demonstrated that MSAF is associated with low Apgar scores (29). However, the study did not present Apgar scores at any particular time-point.…”
Section: Discussionmentioning
confidence: 99%
“…
Meconium stained amniotic fluid (MSAF) is an alarming sign of fetal compromise and predictor of adverse fetal outcomes such as meconium aspiration syndrome and perinatal asphyxia, which leads to perinatal and neonatal morbidity and mortality. [1][2][3] Meconium stained neonates are more prone to develop respiratory distress than neonates born with clear fluid. 1 Meconium stained amniotic fluid significantly increase the rate of maternal complications such as meconium-laden amniotic fluid embolism, intrapartum chorioamnionitis, puerperal endometiritis, wound infection, increased risk of operative delivery and its complication.
…”
mentioning
confidence: 99%
“…of MSAF and more than 4% of MAS infants died accounting for 2% of all perinatal deaths. 1,6,7 Meconium is a germ-free, thick, black-green, odourless material which is first recognized in the fetal intestine around 12 weeks of gestation and stores in the fetal colon throughout gestation. 8 Passage of meconium in the newborn infants is a developmentally programmed incident; normally occurring within the first 24 to 48 hours after birth.…”
mentioning
confidence: 99%
See 1 more Smart Citation